Analysis of the Temperature Effect on the Liquids Viscosity - Anelia Kartika; Aldo Kurniawan; Aditya Kresna (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2023)
This study aims to analyse the effect of temperature on the viscosity of liquid water and cooking oil using the experimental method. Viscosity is a measure of the viscosity of a liquid and can be affected by temperature. In this study, a series of experiments were conducted using water and cooking oil as test materials. The samples were tested for viscosity at different temperatures using a thermometer. Experiments were conducted at several varying temperatures, ranging from room temperature to temperature after heating. The viscosity test results were correlated with temperature and analysed to see the pattern of change. Based on the analysis results, it can be concluded whether the viscosity of water and cooking oil increases or decreases as the temperature increases. In addition, it was found that there is a difference in viscosity response between water and cooking oil to temperature changes. The results of this study show the influence between temperature and viscosity of liquids, especially water and cooking oil.   Keywords: cooking oil, liquid, temperature, viscosity, water.